تأثير الشد المائي على الإنبات ، النمو الخضري وسلامة الأغشية البلازمية لثلاثة أنواع من الكشون Vicia spp. - بشرى خليل المعماري (University of Mosul-college of Basic Education, 2009)
The effect of water stress on germination, vegetative growth and cell membrane stability of leaf tissues for three specie of Vicia, which can be grown at the raining region in the north of Iraq, was studied. The results showed a reduction in the rate and percent of germination. Also a reduction in the characters of vegetative growth (fresh and dry weights), and chlorophyll contents in the leaf tissue under the effect of water stress. The results also showed that the reduction increased with the increase of drought period from (7) to (14) days. As for the stability of cell membrane, the effect of water stress an increase in the electrical conductivity of the efflux medium after boiling and filtering the leaves. The results also showed that the most tolerant of the three species was Vicia dasycarpa.